Optical coherence tomography angiography in miliary tuberculosis - Salil Mehta (Oman Journal of Ophthalmology, 2020)
A 14-year-old female was admitted with a history of high-grade fever. On admission, she underwent a comprehensive clinical, laboratory, and radiological evaluation. A contrast-enhanced computed tomography (CT) scan of the chest revealed multiple, tiny, nodular opacities in a ground-glass pattern bilaterally. Sputum studies were positive for Mycobacterium tuberculosis. Dilated fundus examination revealed multiple, yellow-white, deep choroidal lesions consistent with choroidal tubercles. She underwent optical coherence tomography angiography (OCTA) in both eyes, which revealed normal superficial and deep retinal plexuses but multiple areas of flow void in the choriocapillaris. The optical coherence tomography (OCT) sections showed hyperreflective areas in the choriocapillaris/superficial choroid with absence of choriocapillaris circulation.